Diagnosis and management of intraductal papillary mucinous neoplasms of the pancreas. An Useful Update with a Noteworthy Tip - Bisogni, Damiano; Rossi, Michele; Staderini, Fabio; Freschi, Giancarlo; Manetti, Roberto; Talamucci, Luca (Acta Biomedica Atenei Parmensis, 2021)
Not requested.